Efektivitas Pemanfaatan Ekosistem IoT Pada Mata Kuliah Media Pembelajaran Mahasiswa PGSD Terhadap Peningkatan Keterampilan Abad-21 - ariska, bayu; Erna Muliastrini, Ni Ketut (Adi Widya: Jurnal Pendidikan Dasar, 2026)
This study addresses the urgent need for the integration of advanced technology into the Elementary School Teacher Education curriculum to equip prospective teachers with 21st Century Skills, particularly in the aspects of critical thinking, creativity, and collaboration. The Learning Media course, as the heart of pedagogical innovation, must utilize relevant digital tools, making the utilization of the Internet of Things (IoT) ecosystem the main focus of this study. This study aims to test the effectiveness of the IoT ecosystem in improving 21st Century Skills of PGSD students. The study used a quasi-experimental method with a Nonequivalent Control Group Pretest-Posttest design. The sample consisted of two groups of students selected by purposive sampling: an experimental group that integrated IoT projects and a control group that used conventional media. Data on skill improvement were collected through performance observations and rubric-based assessment instruments, then analyzed using a t-test. The test results showed a significant and substantial increase in the experimental group. The N-Gain calculation showed that the experimental group's score was in the high category (0.78), far exceeding the control group which was in the medium category (0.42). This difference in scores confirms that the integration of the IoT ecosystem into PGSD Learning Media has proven highly effective in facilitating and enhancing students' 21st-Century Skills. The use of IoT is recommended as a standard, adaptive learning model to produce PGSD graduates who are ready to face the challenges of the digital era.